Sarcoma treatment in the era of molecular medicine. Issue 11 (13th October 2020) - Grünewald, Thomas GP; Alonso, Marta; Avnet, Sofia; Banito, Ana; Burdach, Stefan; Cidre‐Aranaz, Florencia; Di Pompo, Gemma; Distel, Martin; Dorado‐Garcia, Heathcliff; Garcia‐Castro, Javier; González‐González, Laura; Grigoriadis, Agamemnon E; et al.
Abstract: Sarcomas are heterogeneous and clinically challenging soft tissue and bone cancers. Although constituting only 1% of all human malignancies, sarcomas represent the second most common type of solid tumors in children and adolescents and comprise an important group of secondary malignancies. More than 100 histological subtypes have been characterized to date, and many more are being discovered due to molecular profiling. Owing to their mostly aggressive biological behavior, relative rarity, and occurrence at virtually every anatomical site, many sarcoma subtypes are in particular difficult‐to‐treat categories. Current multimodal treatment concepts combine surgery, polychemotherapy (with/without local hyperthermia), irradiation, immunotherapy, and/or targeted therapeutics. Recent scientific advancements have enabled a more precise molecular characterization of sarcoma subtypes and revealed novel therapeutic targets and prognostic/predictive biomarkers. This review aims at providing a comprehensive overview of the latest advances in the molecular biology of sarcomas and their effects on clinical oncology; it is meant for a broad readership ranging from novices to experts in the field of sarcoma. Abstract : Sarcomas are heterogeneous and clinically challenging soft tissue and bone cancers. The current article comprehensively reviews recent advances in the molecular characterization of sarcoma subtypes, and describes novel therapeutic targets and biomarkers in this field.